2018
DOI: 10.1016/j.jaim.2017.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Coelogyne cristata Lindley in alleviation of chronic fatigue syndrome in aged Wistar rats

Abstract: The results confirmed the potential therapeutic actions of CCE against experimentally induced CFS in aged rats that might be due to its CNS mediatory antioxidant properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 33 publications
(50 reference statements)
2
4
0
Order By: Relevance
“…In this investigation, the animals were rendered to a single dose of LPS and forced swim trials to induce a state of chronic fatigue.Swiss albino mice were enforced to swim for each 10 minutestime for daily 21 days in a restricted space (jar) from which they cannot escape, and hence, induced to express a characteristic behavior of immobility (fatigue response) thatwas measured on every alternate day.When compared to the LPS group, the Olmesartan administration prompted a noteworthy reduction in the immobility stint on the 7 th , 13 th , and 21 st days.In line with earlier outcomes (Dhir et al2012;Mitra et al 2017), the current ndings depicted that the level of fatigue was elevated in various behavioral tests viz.locomotor activity (in open eld test), anxiety-like symptoms (in elevated zero maze), and memory loss (in plus-maze tests). In this study,the LPS group (fatigue control animal) indicateda reduction in their locomotor activity.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this investigation, the animals were rendered to a single dose of LPS and forced swim trials to induce a state of chronic fatigue.Swiss albino mice were enforced to swim for each 10 minutestime for daily 21 days in a restricted space (jar) from which they cannot escape, and hence, induced to express a characteristic behavior of immobility (fatigue response) thatwas measured on every alternate day.When compared to the LPS group, the Olmesartan administration prompted a noteworthy reduction in the immobility stint on the 7 th , 13 th , and 21 st days.In line with earlier outcomes (Dhir et al2012;Mitra et al 2017), the current ndings depicted that the level of fatigue was elevated in various behavioral tests viz.locomotor activity (in open eld test), anxiety-like symptoms (in elevated zero maze), and memory loss (in plus-maze tests). In this study,the LPS group (fatigue control animal) indicateda reduction in their locomotor activity.…”
Section: Discussionsupporting
confidence: 92%
“…In previous reports, the extent of oxidative strain indicators such as brain TBARS and GSH were shown to be signi cantly correlated with the aforementioned behavioral measures and CFS (Dhir et al2012;Mitra et al 2017).Our ndings showed that Olmesartan reduced TBARS content,whereasit increased GSH levels and thus, improved cellular antioxidant strength in rodent brains, which aptlysubstantiates the proposition that Olmesartantreatment might contribute to managingpro-oxidative molecules in CFS.The HPA axis was triggered by oxidative stress culminated by LPS injection, and this resulted in increased plasma cortisol levels.Cortisol is released when the body is under stress physical or emotional (Dhama et al 2019).When the hypothalamus secretes corticotrophin-releasing hormone (CRH), it kindlesthe pituitary gland for ACTH release. The adrenal glands react to stress by releasing cortisol from the adrenal cortex under the in uence of ACTH.The quantity of cortisol secreted in humans is regulated by a feedback loop that arises from the interplay between the total concentration of plasma cortisol and the pituitary gland.…”
Section: Discussionmentioning
confidence: 89%
“…The effectiveness of the phenanthrene-rich hydroalcoholic extract of pseudobulbs of C. cristata (CCE) in chronic fatigue syndrome (CFS)-induced behavioral changes in aged animals was done by Mitra et al (2018) (Zhao et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Dopamine alteration is the primary cause of ADHD pathology, which has been extensively considered as a significant factor for the progression of the disease (Albrecht et al., 2015; Bijlenga et al., 2019). The substantial clues involved are decreased release of dopamine in the specific areas of brain‐like, striatum, nucleus accumbens, and prefrontal cortex, further decreased dopamine turnover in the frontal cortex, substantia nigra, and ventral tegmental area, as well as reduced dopamine vesicular storage (Bijlenga et al., 2019; Instanes et al., 2018), and increased density of binding sites for the dopamine D1/D5 receptor family in the anterior forebrain (Mitra et al., 2017; Wu et al., 2012).…”
Section: Pathophysiologymentioning
confidence: 99%